Hydrogen can both move or pin dislocations in body-centered cubic metals - Kyung-Shik Kim; Qing-Jie Li; Ju Li; Cemal Cem Tasan (Nature Communications)
Abstract Transition to a hydrogen-based economy requires a thorough understanding of hydrogen interaction with dislocations in metals, especially in body-centered cubic (BCC) steels. Past experimental and computational investigations regarding these interactions often demonstrate two opposing results: hydrogen-induced mobility or hydrogen-induced pinning of dislocations. Through in-situ scanning electron microscopy experiments enabled by a custom-built setup, we address here this discrepancy. Our experiments reveal hydrogen-induced dislocation motion in a BCC metal at room temperature. Interestingly, however, we also observe that the same dislocations are later pinned as well, again induced by the steady hydrogen flux. Molecular dynamics simulations of the phenomena confirm the attraction of the dislocations towards the hydrogen flux, and the pinning that follows after, upon increased hydrogen trapping at the dislocation core. Future experimental or computational studies of hydrogen thus should take into account these different regimes in order to present a full picture of hydrogen defect interactions.